2018
DOI: 10.1074/jbc.ra117.000851
|View full text |Cite
|
Sign up to set email alerts
|

Purification and functional characterization of the vacuolar malate transporter tDT from Arabidopsis

Abstract: The exact transport characteristics of the vacuolar dicarboxylate transporter tDT from Arabidopsis are elusive. To overcome this limitation, we combined a range of experimental approaches comprising generation/analysis of tDT overexpressors, 13 CO 2 feeding and quantification of 13 C enrichment, functional characterization of tDT in proteoliposomes and electrophysiological studies on vacuoles. tdt knock-out plants showed decreased malate and increased citrate concentrations in leaves during the diurnal light-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 47 publications
1
17
0
Order By: Relevance
“…The maximum daily change in citrate content in our N low simulations at day 25 (at maximum growth rate) is 276.1 μmol/gDW, which is comparable with the experimental measurement of 342.32 μmol/gDW (calculated from 22.0 μmol/gFW, based on a conversion ratio from FW to DW for root tissue) under standard condition. Frei et al ( 2018 ) also observed a reciprocal behavior of citrate levels to the changes in malate under diurnal cycle, which is also apparent in our simulation results, both qualitatively and quantitatively, i.e., there was a similar amount of malate accumulation during the day as compared to the amount of citrate accumulates in the dark (see citrate and malate accumulation in Figure 4 ). Aspartate and glycine stored during the day in the leaf were used as the main N sources at night to provide substrates for mitochondrial GS for transamination.…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…The maximum daily change in citrate content in our N low simulations at day 25 (at maximum growth rate) is 276.1 μmol/gDW, which is comparable with the experimental measurement of 342.32 μmol/gDW (calculated from 22.0 μmol/gFW, based on a conversion ratio from FW to DW for root tissue) under standard condition. Frei et al ( 2018 ) also observed a reciprocal behavior of citrate levels to the changes in malate under diurnal cycle, which is also apparent in our simulation results, both qualitatively and quantitatively, i.e., there was a similar amount of malate accumulation during the day as compared to the amount of citrate accumulates in the dark (see citrate and malate accumulation in Figure 4 ). Aspartate and glycine stored during the day in the leaf were used as the main N sources at night to provide substrates for mitochondrial GS for transamination.…”
Section: Resultssupporting
confidence: 86%
“…Some of the citrate was stored at night in vacuole to provide C skeleton in the GS-GOGAT pathway for amino acid biosynthesis during the light phase, which was consistent with the previous experimental and computational studies (Gauthier et al, 2010 ; Cheung et al, 2014 ). A recent study on tDT vacuolar malate transporter also showed quantitative changes in citrate levels between light and dark phases under standard conditions (Frei et al, 2018 ). The maximum daily change in citrate content in our N low simulations at day 25 (at maximum growth rate) is 276.1 μmol/gDW, which is comparable with the experimental measurement of 342.32 μmol/gDW (calculated from 22.0 μmol/gFW, based on a conversion ratio from FW to DW for root tissue) under standard condition.…”
Section: Resultsmentioning
confidence: 92%
“…tDT was considered the main malate transport system at the tonoplast and required for the proper accumulation of malate in Arabidopsis leaves (Emmerlich et al 2003;Hurth et al 2005). tDT was only recently functionally characterized (Frei et al 2018). Highly purified tDT protein showed transport activity as malate and citrate 1:1 in an antiport mode, also accepting fumarate and succinate as substrates (Frei et al 2018).…”
Section: Metabolic Changes Due To Altered Organic Acids Transport In mentioning
confidence: 99%
“…tDT was only recently functionally characterized (Frei et al 2018). Highly purified tDT protein showed transport activity as malate and citrate 1:1 in an antiport mode, also accepting fumarate and succinate as substrates (Frei et al 2018). However, the functional role of tDT in guard cells remained unclear until recently when the metabolic impact of the tDT absence was studied (Medeiros et al 2017).…”
Section: Metabolic Changes Due To Altered Organic Acids Transport In mentioning
confidence: 99%
“…Additionally, they may also serve as counterions for cationic alkaloids to improve their water solubility. 3 , 4 An early indicator of the importance of organic acid salts in nature was given by Sertürner in the 19th century. He isolated morphine as its meconate salt from opium, the dried milky sap from Papaver somniferum .…”
Section: Introductionmentioning
confidence: 99%